Migraine-related healthcare resource use in the emergency department setting: a panel-based chart review in France, Germany, Italy, and Spain. (2nd September 2019) - Vo, Pamela; Gao, Wei; Zichlin, Miriam L.; Fuqua, Eleanore; Fadli, Ela; Aguirre Vazquez, Marta; Tarancón, Thaïs; Mahieu, Nicolas; Maier-Peuschel, Monika; Rossi, Silvia; Naclerio, Mariantonietta; Ritrovato, Daniela; et al.
Abstract: Objective: Migraine is a common, disabling condition typically characterized by severe headache, nausea, and/or light and sound sensitivity. This study assessed migraine-related health resource utilization (HRU) occurring in the emergency room/accident & emergency department (ER/A&E) setting among European patients with 4 or more migraine days per month. Methods: Patient-level clinical and HRU data were collected via chart extraction by ER/A&E physicians in France, Germany, Italy, and Spain. Eligible patients had 4 or more migraine days in the month prior to a migraine-related ER/A&E visit and a history of migraine, among other criteria. The index date for each patient was defined as the date of an ER/A&E visit for migraine on or after January 1, 2013. Physician and ER/A&E characteristics, patient and disease characteristics, treatment history, migraine-medication used, and migraine-related HRU (i.e. procedures) during the ER/A&E visit were assessed. Descriptive analyses were conducted in the pooled population, and a sensitivity analysis was performed by country. Results: A total of 467 eligible patient's charts (120 in France, 120 in Germany, 107 in Italy, and 120 in Spain) were provided by 136 physicians (36 in France, 36 in Germany, 28 in Italy, and 36 in Spain). On average, patients spent nearly 8 hours in the ER/A&E. Approximately 82% of patients received a blood test, 62% received an electrocardiography, and 46% received a cranial computerized tomography scan. Despite the majority of patients already using acute or prophylactic treatment upon visiting the ER/A&E, almost all patients were administered or prescribed migraine treatment during the visit. Approximately 21% of patients were admitted to the hospital, and over half of patients were referred to a neurologist or headache specialist. Conclusions: European patients who had four or more migraine days in the month prior to a migraine-related ER/A&E visit had high HRU associated with the visit.